Management of herbicide-resistant Little seed canary grass (Phalaris minor) by integrating malathion with post-emergence herbicides in wheat crop - Anmol; V. S. Hooda; Meenakshi Sangwan; Aman Karwasra; Gaurendra Gupta (Annals of Agricultural Research, 2023)
A field experiment was conducted with seven post emergence herbicides (clodinafop 9% + metribuzin 20% (RM) (ACM-9), clodinafop 12% + metribuzin 42% (RM) (Shagun), metribuzin, isoproturon, sulfosulfuron, meso+iodosulfuron and pinoxaden) and their combination with malathion at different doses along with weed free and weedy check treatment replicated thrice. Among the sole application of herbicides, significantly taller plants, more dry matter accumulation, higher number of tillers and more LAI were observed under pinoxaden which remained significantly higher than all other herbicides, whereas, the values of these parameters considerably reduced when application of the herbicides were integrated with malathion, except malathion fb pinoxaden. Plots of weed free treatment, pinoxaden at 50 g/ha and malathion fb pinoxaden at 1000 fb 50 g/ha resulted into higher number of tillers per meter row length (mrl) and more LAI. Weed free plots of wheat resulted into higher number of effective tillers (81.6 tillers/mrl) and higher grain yield (5764 kg/ha) and were followed by pinoxaden at 50g/ha treatment. The weed density and dry weight of P. minor was considerably reduced along with higher weed control efficiency when the herbicides were applied with their integration with malathion as compared to solitary application of herbicides.